Secure control plane for SDN using Bayesian Stackelberg games - Zhen-ping LU; Fu-cai CHEN; Guo-zhen CHENG (网络与信息安全学报)
A dynamic scheduling controller in SDN control layer was proposed by dynamically transform heteroge-neous controlled in order to increase the difficulty of the attacker.Firstly,a dynamic scheduling method based on Bayesian Stackelberg games the attacker and defender were game participation on both sides,obtained the equili-brium,which guided the scheduling strategy.Secondly,introducing a self-cleaning mechanism,it improved the gain of the control layer security combined with game strategy form closed-loop defense mechanism.The experiments described quantitatively based on the game strategy compared with traditional safety control layer to deploy a single controller and adopt the strategy of random scheduling profit gain of the controller,and self-cleaning mechanism could make the control plane to be in a higher level of security.